STYLISTIC AND PRAGMATIC FUNCTIONS OF LANGUAGE TOOLS IN TRANSLATING FROM ENGLISH INTO UZBEK - Khayrieva Madina Ilhomovna; Nurullayeva Madina Rashidjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article provides a comprehensive overview of the challenges and methodologies involved in translation, particularly from English to Uzbek. It begins by highlighting the complexities faced by translators due to differences in language structure and meaning between the source and target languages. While automatic translation tools are available, they often fail to capture the nuances of the original message accurately. The importance of maintaining fidelity to the original message, without adding or subtracting information, is emphasized, underscoring the translator's role in bridging linguistic and cultural gaps.